Dosimetric verification of inverse planned step and shoot multileaf collimator fields from a commercial treatment planning system - MacKenzie, M. A. (J Appl Clin Med Phys, 2002)
An inverse treatment planning (ITP) module on a commercial treatment planning system (TPS) (Helax AB, Uppsala, Sweden) is being used for an in‐house clinical trial for treatment of nasopharyngeal cancer with contralateral parotid sparing. Intensity modulated radiation therapy (IMRT) fields are delivered by step and shoot multileaf collimator (MLC) with a DMLC enabled Varian 2300 CD (Varian Associates, Palo Alto, CA). A series of testing procedures have been devised to quantify the modeling and delivery accuracy of routine clinical inverse planned IMRT using Helax TMS and the Varian step and shoot MLC delivery option. Testing was done on specific aspects of the TPS modeling germane to DMLC. Measured relative dose factors (head scatter plus phantom scatter) for small MLC fields, normalized to a [Formula: see text] non‐MLC field, were found to differ by [Formula: see text] from the TPS values for the smallest of the fields tested. Relative distributions for small off axis fields were found to be in good agreement. A process for the routine clinical verification of IMRT fields has been implemented. Each IMRT field in an inverse plan is imported into a flat water tank plan and a “beam's eye view” (BEV) dose distribution is generated. This is compared to the corresponding measured BEV dose distribution. The IMRT verification process has also been performed using an anthropomorphic phantom. Large clinical fields (i.e., greater than 14.5 cm in the leaf direction) caused difficulties due to a vendor specific machine restriction, and several techniques for dealing with these were examined. These techniques were (i) the use of static stepping of closed junctions, (ii) the use of two separate IMRT fields for a given gantry angle, and (iii) restricting the overall maximum field size used. The overall process has allowed implementation of an in‐house protocol for IMRT use on an initial clinical site. Results of the verification measurements for the first ten patients treated at this center reveal an average maximum dose per IMRT field delivered of 71.0 cGy, with a mean local deviation from the planned dose of – 1.2 cGy, and a standard deviation of 2.4 cGy. PACS number(s): 87.53.Dq, 87.53.Tf